Internal Quality Assurance System Management in Improving School Performance - Ahmad Khori; Hamdan Hidayat; M. Mujib Qulyubi; Faizal; Miko Ilya Viskar (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2026)
This study aims to analyze the implementation of Internal Quality Assurance System Management (SPMI) in an effort to improve school performance at SMAS Kartika X-1 and SMA Negeri 86 South Jakarta. This study employs a qualitative approach, utilizing a case study method, where data are collected through interviews, observations, and document reviews. The results of the survey indicate that SPMI significantly contributes to improving school performance through comprehensive and participatory planning, implementation supported by teacher training and technology, data-driven systematic evaluation, and responsive follow-up. The novelty of the research lies in the resulting collaborative model, which emphasizes the active synergy of all stakeholders principals, teachers, students, and parents in creating a sustainable culture of quality. Constraints, such as resource limitations and resistance to change, can be overcome through collective commitment and capacity-building strategies. In conclusion, SPMI is a strategic tool to create an educational ecosystem that is accountable and oriented towards continuous improvement. As policy recommendations, it is necessary to strengthen school leadership, invest in teacher professional development, and integrate technology in the quality monitoring system to support the effectiveness of SPMI at the school level.